DIPG-25. KETOGENIC DIET IN DIFFUSE INTRINSIC PONTINE GLIOMA IN CHILDREN: A RETROSPECTIVE STUDY INVESTIGATING THE FEASIBILITY. (4th December 2020) - Perez, Alexandre; Nathan, Janak; El-Ayadi, Moatasem; Korff, Christian; Ansari, Marc; von Bueren, André
Abstract: PURPOSE: Diffuse Intrinsic Pontine Glioma (DIPG) is one of the most devastating diseases amongst children with cancer, thus novel strategies are urgently needed. We aimed to retrospectively evaluate the feasibility of the carbohydrate restricted ketogenic diet (KD) in DIPG patients. METHODS: Searches of MEDLINE and Embase identified four publications meeting the inclusion criteria (diagnosis of DIPG and exposition to a KD ≥ 3 months). One additional case was identified by contact with experts. The minimal feasibility criteria were defined as the ability to use the KD for ≥ 3 months. Individual patient data were extracted from the publications or obtained from investigators. RESULTS: Five patients (males, n=3; median age 4.4 years; range, 2.5–17 years) met the inclusion criteria (one patient – identified and not included - was on KD < 3 months due to disease progression). Further feasibility analyses showed a duration of the KD of ≥ 3 months and less than 7 months (n=2), > 7 months and less than 1 year (n= 2), and two years (n=1), respectively. CONCLUSION: These results – based on a small patient population – suggest that the KD appears to be a feasible treatment option for children with DIPG. The potential duration of the KD is limited by the aggressive clinical behavior of DIPG. The safety analysis is currently being retrospectively assessed. These data should encourage further studies on a larger scale; ideally assessing the impact of the KD in DIPG patients in a randomized controlled trial.